1988
DOI: 10.1080/00288233.1988.10421368
|View full text |Cite
|
Sign up to set email alerts
|

Influence of time of application on the fate of15N-labelled urea applied to dairy pasture

Abstract: Urea eSN-enriched) was applied at 50 kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…This suggests that N was stored in the soil in a form not measured as soil extractable inorganic N and/or plant material remaining in the plot. Tracer studies have shown that considerable fertilizer N can be incorporated into organic fractions in the soil (Bristow et al 1987;Ledgard et al 1988;Malhi 1995;Stevens et al 1986), and that the sizes of these fractions increase with time. Whitehead et al (1990) estimated N released by mineralization in the first year after cultivation increased from 70 kg N ha -1 in a 1-yr-old stand to 300 kg N ha -1 in a 15-yr-old stand.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that N was stored in the soil in a form not measured as soil extractable inorganic N and/or plant material remaining in the plot. Tracer studies have shown that considerable fertilizer N can be incorporated into organic fractions in the soil (Bristow et al 1987;Ledgard et al 1988;Malhi 1995;Stevens et al 1986), and that the sizes of these fractions increase with time. Whitehead et al (1990) estimated N released by mineralization in the first year after cultivation increased from 70 kg N ha -1 in a 1-yr-old stand to 300 kg N ha -1 in a 15-yr-old stand.…”
Section: Discussionmentioning
confidence: 99%
“…At the second harvest, the 600-900 mm depth was also sampled for the 200kgNha ~ treatment. Subsamples were dried (60°C), digested using a reduced iron method to include nitrate and analysed for total N and 15N (Ledgard et al, 1988). Subsamples of moist soil were also extracted with 2 M KCI and analysed for inorganic N and ~SN (Ledgard et al, 1988).…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
“…N-losses under urine patches via nitrogen leaching are of great concern, whereas under dung patches N mineralization-immobilization processes dominate (Thompson and Fillery 1997). The total amount of N leached under urine patches varies between 18 and 58% of the applied N, depending on the soil texture (Clough et al 1998), application time (Cuttle and Bourne 1993;Ledgard et al 1988;Di and Cameron 2002;Stout 2003), the amount of urine (Thompson and Fillery 1997;Stout 2003), and the botanical composition of the pasture (Loiseau et al 2001). An estimation of the contribution of dung to N-losses under pasture is difficult as the results from incubation experiments (Barrow 1961;Takahashi et al 2004) are not translatable to field conditions.…”
Section: Introductionmentioning
confidence: 98%